Fear of crime in the context of gender and ambivalent sexism in Turkey - Türk,Burcu et al (International Sociology)
the participants over 18. In this context, participants responded to the questions of the sociodemographic survey, gender perception scale, ambivalent sexism inventory, and fear of crime scale. According to the findings, the female participants were more frequently the victims of crime than men and more often exposed to hate crimes, sexual harassment, and domestic violence. Besides, the mean score of women s fear of crime scale was found to be significantly higher than that of men. The mean score of the gender perception scale of female participants was significantly higher than that of men. A positive and significant relationship was found between the scores of gender perception and fear of crime scales. In other words, as gender perception increases, the fear of being a victim of a crime also increases.- Reproduced
Keywords: Ambivalent sexism, Benevolent sexism, Fear of crime, Gender perception, Hostile sexism